Proceedings of 15th International Conference on Distributed Computing Systems
DOI: 10.1109/icdcs.1995.500001
|View full text |Cite
|
Sign up to set email alerts
|

A new protocol for bandwidth regulation of real-time traffic classes in internetworks

Abstract: A novel bandwidth regulation mechanism is proposed which improves the ability of a packet-switching network to cope with multiple real-time and non-real-time tra c classes. The mechanism achieves regulation of link bandwidth at two levels. At the rst level, bandwidth is dynamically regulated b etween di erent tra c classes. The concept of`inter-class regulation' i s i ntroduced which enforces that the bandwidth left unused by a tra c class is divided among tra c classes with high bandwidth demands. At the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…There is one TReg daemon at each host and TReg daemons at di erent h o s t s communicate with each other to determine the maximum rate of each source. In a previous study 6] it was shown that these mechanisms are su cient t o e ectively support relative QoS in a general packetswitched network.…”
Section: Design Of the Treg Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…There is one TReg daemon at each host and TReg daemons at di erent h o s t s communicate with each other to determine the maximum rate of each source. In a previous study 6] it was shown that these mechanisms are su cient t o e ectively support relative QoS in a general packetswitched network.…”
Section: Design Of the Treg Protocolmentioning
confidence: 99%
“…Theoretical concepts for relative QoS have been studied before 1, 5 , 6 , 7 ] . F or example, in the schemes investigated in 5,6], all ows whose throughput is limited by the same network resource have identical throughput constraints. Obviously, the performance guarantees with relative QoS are weaker than those obtainable with absolute QoS.…”
Section: Introductionmentioning
confidence: 99%